2022
DOI: 10.1021/acs.jpcc.2c03364
|View full text |Cite
|
Sign up to set email alerts
|

Negative Differential Resistance in the Au-Coated CH3NH3PbBr3 Perovskite Photodetectors with Fast Response

Abstract: Lead halide perovskites have emerged as attractive photoelectric materials owing to their excellent performance, which demonstrates great potential for application in the optoelectronic field. A basic understanding of the photogenerated carrier transport in perovskite photodetectors is critical to achieving high-performance devices. Here, we reported the ultraviolet photodetectors with a fast response based on the Au-coated CH3NH3PbBr3 perovskite nanowires, which were grown by an in situ solution method. Inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Further tests revealed that this change in the shape of the light pulse curve is a complex behavior that depends simultaneously on ion migration, light intensity, and applied voltage. [ 47,48 ] Figure 4e demonstrates the good switching characteristics of the photodetector for different light‐intensity irradiation. Figure 4f shows the effective modulation of the photoswitching characteristics with different bias voltages, which still exhibits a certain degree of photoswitching response even at 0 V. In addition, the device shows good stability under long‐term light pulse operation, as shown in Figure S5 (Supporting Information).…”
Section: Resultsmentioning
confidence: 98%
“…Further tests revealed that this change in the shape of the light pulse curve is a complex behavior that depends simultaneously on ion migration, light intensity, and applied voltage. [ 47,48 ] Figure 4e demonstrates the good switching characteristics of the photodetector for different light‐intensity irradiation. Figure 4f shows the effective modulation of the photoswitching characteristics with different bias voltages, which still exhibits a certain degree of photoswitching response even at 0 V. In addition, the device shows good stability under long‐term light pulse operation, as shown in Figure S5 (Supporting Information).…”
Section: Resultsmentioning
confidence: 98%
“…Such as the solution growth method, electrodeposition technique, and membrane transfer method. [148][149][150][151][152][153][154] Fifth, the performances of laser power, divergence angle, and mode modulation should be improved. Because of the laser power, divergence angle and mode modulation are the challenges for the integration and practicability of the electrically pumped nanolasers.…”
Section: Current Challenge and Future Prospectmentioning
confidence: 99%
“…Such as the solution growth method, electrodeposition technique, and membrane transfer method. [ 148–154 ]…”
Section: Current Challenge and Future Prospectmentioning
confidence: 99%